Uncovering economic impacts and dynamics of European energy policy: Evidence from DEMATEL, panel data, and cluster analysis - Aldona Kluczek; Agnieszka Woźniak; Patrycja Żegleń (PLoS ONE, 2025)
This study analyzes the relationship of national diversity in energy policies between economic outcomes amid changing energy prices, climate regulations, and technological innovations across European countries. Using DEMATEL, panel data econometric models, and cluster analysis, the research three interrelated questions: whether environmental regulations can simultaneously support economic performance and innovation; how energy prices and climate policies affect inflation, economic growth, and unemployment; and whether a hybrid causal framework can reveal deeper feedback dynamics across policy, innovation, and macroeconomic variables, The results identify significant relationships between technological innovations, energy prices, climate regulations, and inflation. The analysis reveals that energy prices influence R&D expenditure, with both positive and negative effects depending on timing. Climate regulations and inflation also significantly impact technological innovations. The findings emphasize the need for strategic planning and investment in technology to manage energy prices and climate policies effectively. The study suggests that stable, innovation-oriented regulatory frameworks are more effective than short-term interventions such as subsidies or price caps in promoting green technologies, reducing economic volatility, and supporting the transition to sustainable energy systems. Limitations include the exclusion of variables such as institutional quality, consumer behavior, and readiness for energy storage infrastructure. Further research with extended time series and localized data is recommended to deepen understanding and support resilient energy policy development.